Nilai-Nilai Pendidikan Islam dalam Buku “Orang Maiyah” Karya Emha Ainun Nadjib - Wardatul Ummah (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Today's education can be said to be alarming, as a person who is concerned in education we must not be trapped in material things, for example we judge the level of education of a person from the degree he has, how many degrees he has and where he got it, but today we do not see a more substantial state of